Consideration of ionic polymer materials as flapping mechanisms for micro-air vehicle - Akle, Barbar (2003)
Ionic Polymers are soft actuators that perform large bending and flapping deflections when a small voltage is applied across their thickness. Due to their mechanical similarities to biological muscles and their large flapping displacement capabilities we were interested in studying the possibility of their use in flapping Micro Air Vehicle (MAV) application, as engines, controllers and sensors. Three main difficulties had to be overcome before ionic polymers could be considered for this application. The first difficulty was the small actuated force; the second difficulty was the non-linearity and time variation properties, while the articles is tacking technique that would potentially solve those difficulties. The multilayer ionic polyners are first characterized in series and paralel electrical connections., and then ad combined sensor-actuator stacks. Furthermore, a finite elemtnet analysis modeling technique capable of modeling themultilayer ionic polymers is illustrated, and used to design ionic polymers actuated flapping wings.